PENYUSUNAN ALTERNATIF PENGELOLAAN SUMBER DAYA AIR TAWAR DI PULAU NUNUKAN BERBASIS DATA INDERAJA DAN SISTEM INFORMASI GEOGRAFIS - F. Sri Hardiyanti Purwadhi; Nanik Suryo Hariyani (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2007)
This paper explores ome of the experiences of freshwater resources management alternative in Nunukan Island, using remote sensing technologies and geographic information system. Freshwater resources in many small islands depend upon the rainfall. Nunukan Island is a small island with problems of freshwater severe. Nunukan Island have very high population densities in the urban area that place great stress on their water resources. The main influences on the natural freshwater resources are physiography, climate, rainfall, evaportranspiration, and geologycal condition. Freshwater resources management alternative in this study base on approach of water, augmenting freswater for indicate water suplly, and water efficiency for general purposes.